DO SHARIA AND NON-SHARIA LISTING SECURITIES INVESTORS RESPOND DIFFERENTLY TO TAX AVOIDANCE? - Anggraini, Puspita Ghaniy; Ayu, Putri Werdina Ciptaning; Saragih, Arfah Habib; Dharsana, Muhammad Try (Jurnal Akuntansi dan Keuangan Indonesia, 2021)
This study empirically tests the behavior of Sharia and non-Sharia securities investors towards corporate tax avoidance. If Sharia securities investors make investment decisions considering Sharia principles, corporate tax avoidance should be viewed as a bad practice which is contradictory to Sharia principles and it is intolerable for this type of investors. Using companies from the financial industry for the period of 2007-2018, the final sample comprises 378 observations for Sharia securities and 167 observations for non-Sharia securities. This secondary data research is conducted by applying moderated regression analysis to test the hypothesis. This study finds that the market responses regarding corporate tax avoidance practices on average are lower (higher) for Sharia (non-Sharia) securities.